Sustainable development from a human rights perspective and the challenges it represents for the Caribbean SIDS : (a discussion paper) - Geiser, Hans (ECLAC. Sustainable Development Unit Port of SpainTT, 2010)
Examines the extent to which the pursuit of sustainable development in the Caribbean Small Island Developing States (SIDS) is guided by human rights considerations and, more specifically, what extent human rights principles, norms and standards are being integrated and mainstreamed in development programmes and projects, following a rights-based approach to development.